Integrated Microbiome and Metabolome Analysis Reveals Correlations Between Gut Microbiota Components and Metabolic Profiles in Mice With Mitoxantrone-Induced Cardiotoxicity - Zhang Q; Liang D; Zhang C; Ye L; Sun P; Zhu H; Zhao Y; Li Y; Guan Y; Zhang H (Drug Design, Development and Therapy)
Qing Zhang,1 Deshuai Liang,2 Chengfang Zhang,3 Ling Ye,4 Ping Sun,4 Hongli Zhu,4 Yongqin Zhao,4 Yuewen Li,4 Yun Guan,4 Haiguo Zhang4 1College of Clinical Medicine, Jining Medical University, Jining, 272013, People’s Republic of China; 2Department of Pharmacy, Jining NO. 1 People’s Hospital, Jining, 272000, People’s Republic of China; 3Department of Clinical Laboratory, Jining NO. 1 People’s Hospital, Jining, 272000, People’s Republic of China; 4Department of Hematology, Jining NO. 1 People’s Hospital, Jining, 272000, People’s Republic of ChinaCorrespondence: Haiguo Zhang; Yun Guan, Jining NO. 1 People’s Hospital, 6 Jiankang Road, Jining Shandong, 272000, People’s Republic of China, Tel/Fax +86-0537 2257626 ; +86-0537 2087093, Email wfmchero@126.com; gyuanun1989@163.comPurpose: Mitoxantrone (MTX) is largely restricted in clinical usage due to its significant cardiotoxicity. Multiple studies have shown that an imbalance in the gut-heart axis plays an important role in the development of cardiovascular disease (CVD). We aim to explore the possible correlations between gut microbiota (GM) compositions and cardiometabolic (CM) disorder in MTX-triggered cardiotoxicity mice.Methods: MTX cumulative dose of 6 mg/kg was administered to healthy Kunming male mice to trigger cardiotoxicity, with 1 mg/kg twice weekly for a duration of 3 weeks. Plasma CK-MB and LDH levels were determined, and the heart tissue histopathology was assessed, followed by utilizing an integrated liquid chromatography-mass spectrometry (LC-MS)-based heart metabolomics study alongside the 16S ribosomal RNA (rRNA) sequencing method to assess MTX impact on GM and CM profiles in mice, establishing associations between GM and CM profiles through the Pearson correlation coefficient calculation.Results: MTX caused CK-MB and LDH level elevations and cardiotoxicity in our mouse model. MTX primarily affected the processes of protein digestion and absorption, mineral absorption, membrane transport, production of aminoacyl-transfer RNA (tRNA), metabolism of nucleotides, lipids, and amino acids, as well as autophagy. Additionally, MTX increased Romboutsia, Enterococcus, and Turicibacter abundances and lowered norank_f__Muribaculaceae, Alistipes, Odoribacter, norank_f__Lachnospiraceae, norank_f__Ruminococcaceae, norank_f__Oscillospiraceae, unclassified_f__Ruminococcaceae, NK4A214_group, Colidextribacter, norank_f__norank_o__Clostridia_vadinBB60_group, Rikenella, and Anaerotruncus abundances. The correlation analyses showcased variations in the abundance of diverse flora, such as Romboutsia, Enterococcus, Turicibacter, and norank_f__Muribaculaceae, which were related to MTX-induced cardiac injury.Conclusion: Our study supports the claim that MTX provokes cardiotoxicity by modifying CM and GM profiles. Our results offer new possibilities for controlling MTX-triggered cardiotoxicity.Keywords: 16S ribosomal RNA, liquid chromatography-mass spectrometry, mitoxantrone, cardiotoxicity